2007
DOI: 10.1021/je7003935
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Phase Behavior of Ionic Liquids with Water and 1-Octanol and Modeling of 1-Octanol/Water Partition Coefficients

Abstract: This study examines the effect of structural components of an ionic liquid (IL), including the choice of the anion, alkyl chain length on the cation, and substitution on the cation, on the mutual solubility with water and with 1-octanol. This is important because ionic liquids have been shown to be good replacements for organic extraction solvents in some liquid separations. In addition, we use the measured data to predict 1-octanol/water partition coefficients for the ionic liquids using the nonrandom two liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 28 publications
6
74
1
Order By: Relevance
“…The solubility of water in the IUPAC sample of [C 6 Chapeaux et al [26] also reported (at T = 296.6 K) the mass fraction solubility of the IUPAC sample in water determined by coulometric Karl Fischer titration. The estimated uncertainty in w(H 2 O) was 1ؒ10 -4 .…”
Section: Vle Studies With Other Compoundsmentioning
confidence: 99%
“…The solubility of water in the IUPAC sample of [C 6 Chapeaux et al [26] also reported (at T = 296.6 K) the mass fraction solubility of the IUPAC sample in water determined by coulometric Karl Fischer titration. The estimated uncertainty in w(H 2 O) was 1ؒ10 -4 .…”
Section: Vle Studies With Other Compoundsmentioning
confidence: 99%
“…The solubility of water in the IUPAC sample of [C 6 mim][NTf 2 ] was studied by Chapeaux et al [63] and Widegren and Magee [4] using coulometric Karl Fischer titration. Additional results for non-IUPAC samples were published earlier by Fitchett et al [26] and McFarlane et al [64].…”
Section: Mixture Properties (Liquid-liquid Equilibria)mentioning
confidence: 99%
“…For a systematic understanding of the properties of IL-W two-phase systems, the hydrophobicity of ILs and its constituent ions has been experimentally studied through the partition coefficients of ILs between octanol and water, 227,233,234 and reverse-phase high-performance liquid chromatography. [235][236][237][238] These approaches provide a relative magnitude of the hydrophobicity for a series of cations, or that of anions.…”
Section: ·3 Hydrophobicity Scale Of Ionsmentioning
confidence: 99%
“…225,233,234,242 . 32,169,242,243 By and large, the linearity also holds for the change in the solubility of W in the ILs with the change in the anionic species.…”
Section: ·3 Hydrophobicity Scale Of Ionsmentioning
confidence: 99%